PENGARUH INSENTIF DAN REWARD TERHADAP PENINGKATAN PRESTASI KERJA KARYAWAN PT. PLN (PERSERO) WS2JB - Umi Hasanah (JURNAL KOMPETITIF, 2014)
ABSTRACT Study entitled "The Effect of Incentive and Reward Against Job Performance (Study on PT. PLN ( Persero ) WS2JB ) " was held on May 10 -30 July 2013 . Providing incentives for employees is very important in improving employee performance . This study aims to : 1 ) determine the influence of variables simultaneously Incentive and Reward ( x ) on Employee Job Performance ( y ) determine the dominant influence between variables Incentive and Reward ( x ) against the employee Job Performance . The method used is to use the questionnaire as a data collection tool to be distributed to respondents with a sample of 66 employees . . From simple linear regression test results obtained F - value of 22.893 count is greater than the F - table value of 3.49 at significant level 0.05 then Ho is rejected which means that the performance variable ( y ) is significantly influenced by variables Incentive and Reward ( x ) and Incentives . Coefficient ( R Square ) shows the number 0.450 which means that the variable Work Performance ( y ) by 45 % influenced by variables Incentive and Reward ( x ) while the remaining 55 % are influenced by variables other than the independent variable in this study . Thus the variable Incentives and Reward at PT . PT PLN ( Persero ) WS2JB there are strong ties to the Job Performance variable ( y ) . The conclusion from the research is that there is influence between variables incentives and rewards on work performance ( y ) . So the advice given is : In accordance with the results of research and discussion, it is advisable for the company to pay more attention to incentives and rewards ( x ) because it is proven to affect employee performance ( y ) . Keywords: Incentive and Reward , Job Performance